Early-Outcome Differences between Acute and Chronic Periprosthetic Joint Infections-A Retrospective Single-Center Study - Yasmin Youssef; Elisabeth Roschke; Nadine Dietze; Anna-Judith Dahse; Iris F. Chaberny; Donald Ranft; Christina Pempe; Szymon Goralski; Mohamed Ghanem; Regine Kluge; Christoph Lübbert; Arne C. Rodloff; et al. (MDPI AG, 2024)
Periprosthetic joint infections (PJI) are serious complications after arthroplasty, associated with high morbidity, mortality, and complex treatment processes. The outcomes of different PJI entities are largely unknown. The aim of this study was to access the early outcomes of different PJI entities. A retrospective, single-center study was conducted. The characteristics and outcomes of patients with PJI treated between 2018 and 2019 were evaluated 12 months after the completion of treatment. Primary endpoints were mortality, relapse free survival (RFS) and postoperative complications (kidney failure, sepsis, admission to ICU). A total of 115 cases were included [19.1% early (EI), 33.0% acute late (ALI), and 47.8% chronic infections (CI)]. Patients with ALI were older (p = 0.023), had higher ASA scores (p = 0.031), preoperative CRP concentrations (p = 0.011), incidence of kidney failure (p = 0.002) and sepsis (p = 0.026). They also tended towards higher in-house mortality (ALI 21.1%, 13.6% EI, 5.5% CI) and admission to ICU (ALI 50.0%, 22.7% EI, 30.9% CI). At 12 months, 15.4% of patients with EI had a relapse, compared to 38.1% in ALI and 36.4% in CI. There are differences in patient characteristics and early outcomes between PJI entities. Patients with EI have better early clinical outcomes. Patients with ALI require special attention during follow-up because they have higher occurrences of relapses and postoperative complications than patients with EI and CI.